One Marriage One Tree Policy in Jombang: Institutional and Community Responses to Ecological Responsibility in Islamic Marriage Administration - Alhabibah, Safira; Rifqi, Muhammad Jazil; Nasrul, Muhammad Amrullah Drs (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2026)
Marriage in Islam serves as the foundation of family formation with evolving social responsibilities, including ecological responsibility. In this context, the One Marriage One Tree policy in Jombang introduces innovation in marriage services by transforming marriage administration into a medium for ecological awareness, raising questions about relationships among administrative innovation, public responsibility, and the legitimacy of Islamic law. This socio-legal study employs an empirical legal method with a sociological approach. Data were collected through interviews with officials from three Religious Affairs Offices (KUA) in Diwek, Jogoroto, and Kabuh, an official from the Environmental Agency, and prospective brides, supported by document analysis and analyzed using Islamic law and structural functionalism. The findings reveal that policy implementation varies according to local conditions. KUA Diwek demonstrates a more established pattern with organized planting locations, KUA Jogoroto represents collective governance through scheduled and documented practices, and KUA Kabuh applies a flexible pattern adapted to dry-land conditions. These variations are supported by coordination with village authorities, institutional assistance from KUA personnel, and gradual acceptance among prospective couples. Within Islamic law, tree planting constitutes a maṣlaḥah-based administrative measure rather than a legal requirement of marriage. Through Talcott Parsons’ structural functionalism, the policy fulfills AGIL functions by facilitating institutional adaptation, ecological goal attainment, social integration, and new ecological value formation. The significance of this study lies in showing that Islamic family administration can become a platform for legal awareness, ecological education, and family-based environmental responsibility without altering the normative structure of marriage law.